Predictors of patient relevant outcome after total hip replacement for osteoarthritis: a prospective study. Issue 10 (12th September 2003) - Nilsdotter, A-K; Petersson, I F; Roos, E M; Lohmander, L S
Abstract : Objectives: To investigate prospectively long term patient relevant outcomes after unilateral total hip replacement (THR) for osteoarthritis (OA). To identify non-responders to this intervention and patient related predictors of unsatisfactory outcome. Methods: A case-control study comparing health related quality of life of 219 patients (mean age 71) after THR with that of a matched reference group of 117 subjects without hip complaints recruited from the community. Patients and reference group answered SF-36 and WOMAC questionnaires preoperatively, at 3, 6, 12 months, and at 3.6 years (range 26–65 months) postoperatively. Supplementary questions were asked at the final follow up. Results: 198/211 (94%) of the patients and 83/109 (76%) of the reference group participated at the final follow up. At follow up, the only difference between the two groups in the SF-36 was physical function, where patients scored worse. Patients also reported worse WOMAC function. 31% of the patients had improved by <10/100 WOMAC score points for pain and/or function at final follow up, compared with preoperatively. More pain preoperatively and higher age and postoperative low back pain predicted a worse outcome in WOMAC function. Conclusion: 3.6 years after THR for OA, health related quality of life was similar for patients and reference group except for function, where patients had worse function. Higher age and more pain preoperatively predicted a poor outcome. Patients with hip OA with musculoskeletal comorbidities, such as low back pain and OA of the non-operated hip, have less long term functional improvement after THR.